Effect of polyglycerol esters additive on palm oil crystallization using focused beam reflectance measurement and differential scanning calorimetry. (1st January 2017) - Saw, M.H.; Hishamuddin, E.; Chong, C.L.; Yeoh, C.B.; Lim, W.H.
Highlights: Effect of PGEmix-8 on palm oil crystallization was studied using FBRM and DSC. FBRM is able to detect nucleation onset and changes in crystal size distribution. All results show increased inhibitory effect on crystal growth with more PGEmix-8. 0.7% (w/w) PGEmix-8 enhances nucleation and retards crystal growth. Abstract: The effect of 0.1–0.7% (w/w) of polyglycerol esters (PGEmix-8) on palm oil crystallization was studied using focused beam reflectance measurement (FBRM) to analyze the in-line changes of crystal size distribution during the crystallization. FBRM results show that 0.1–0.5% (w/w) of PGEmix-8 did not significantly affect nucleation but slightly retarded crystal growth. The use of 0.7% (w/w) additive showed greater heterogeneous nucleation compared to those with lower dosages of additive. Crystal growth was also greatly reduced when using 0.7% (w/w) dosage. The morphological study indicated that the palm oil crystals were smaller and more even in size than when more additive was added. Isothermal crystallization studies using differential scanning calorimetry (DSC) showed increased inhibitory effects on palm oil crystal growth with increasing concentration of PGEmix-8. These results imply that PGEmix-8 is a nucleation enhancing and crystal growth retarding additive in palm oil crystallization at 0.7% (w/w) dosage.